Die deuntjie draal": Op die spoor van Koos du Plessis - Boshoff, P. B. (Hervormde teologiese studies, 1995)
'The melody lingers on': On the trail of Koos du Plessis. The angst experienced by Du Plessis assumes the form of a problem on which he ponders in his poetry.The questions that he poses differ in form only from the bewilderment experienced by the narve. The poetic art of the singer and the faltering intimations of the despondent heart are two languages that express the same human anxiety. The truth of both languages lies therein that the one can develop into the other. This article listens from a Christian viewpoint. Themes that are dealt with are wandering, the goldy Other, past and future, anxiety, waiting, dreaming and temptation.